Rules of Fixed Assets Accounting Should Be Changed - V. G. Get’man (Учёт. Анализ. Аудит)
Nowadays the role of accounting in managing the economy of businesses is increasing. Accounting is one of the main information sources for making managerial decisions in organizations. However its current model calls for improvement of accounting of production capacity of economic entities namely accounting of fixed assets. The article aims at substantiating and developing the recommendations on how to improve the organization and methodology of fixed assets accounting. The existing legal norms and rules make the methodological basis for the study. The general scientific methods of comparison, deduction, analysis and synthesis are used in the study. The critical analysis of existing regulations on accounting of the fixed assets reveals substantial drawbacks related to accounting of fixed assets at the end of the normative useful life if these assets are still used in production; costs of fixed assets modernization and costs of their major repair. The author makes certain proposals on the amendment of existing rules of fixed assets accounting in order to make the reporting of the economic processes in this area more realistic and transparent. These proposals should be considered in the first run by the specialists in accounting methodology when developing a new standard.